Research and implementation of network architecture of LSN DCI EVPN VxLAN - Yongming YAN; Liang ZUO; Bin XU; Haifeng XU; Kechuang YE (Dianxin kexue)
With the rise of virtualization technology,the architecture of traditional data center is disrupted.There exit a large number of interconnected needs among the data centers,such as data center active-active,data center redundancy,data synchronous backup,data migration,integrated data store,shared virtual resource pool,virtual machine drift and so on.Thereby,a large amount of east-west flow was generated,it is necessary to build a reliable,flexible,secure,and easy to deploy layer-2 and layer-3 network to meet the requirement of DCI (data center interconnection).The network architecture of EVPN VxLAN was analyzed,there hasn’t been successful large-scale business case for implementation of multi-vendor DCI EVPN VxLAN networking.Combined with current status of LSN data center of Shanghai Telecom,the deployment of DCI via existing network was proposed and achieved.